Quality of service (QOS) in software defined networking (SDN) using bandwidth shaping in cloud computing / Mohd Izham Zamri - Zamri, Mohd Izham (2014)
This chapter explains the overview of the research work starting from the research background. Next, followed by the problem statement will be discussing on the needs of this study to be carried out. After that, research questions, objective, the scope of study, significance of study and organization of thesis will be explained accordingly